STUDENT PERCEPTIONS IN THE APPLICATION OF HYBRID LECTURES WITH COGNITIVE ABILITY IN LEARNING INNOVATION COURSES (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to determine student perceptions in the application of Hybrid lectures and the relationship between hybrid lectures and students' cognitive abilities in the Learning Innovation course.This type of research uses mixed methods research methods. The designs in this study were sequential explanatory designs. The sampling technique used purposive sampling. The sample in this study was the 3rd semester students of class A3 in the PGSD study program, Muhammadiyah University of Sidoarjo, totaling 40 students, consisting of 92.5% female and 7.5% male. The instruments used in this study were observation sheets, interview sheets, questionnaire sheets, student cognitive ability test sheets. From the findings of qualitative data, it shows that students' perceptions in Hybrid lectures are in the good category with an average value of 2.91. As much12.5%, strongly agree, 72.5% agree, 13%, disagree and 2.5% disagreewith the implementation of hybrid lectures on campus. Student perceptions in Hybrid lectures get understanding of the lecture material with the percentage of student answers strongly agreeing 12.5%, agree 70%, disagree 18%, and disagree 0%, with resultsan average of 2.95 categories of good student responses. Further research related to students' cognitive abilities was obtained. The result of simple correlation (r) of 0.479 has a relationship with a moderate level of relationship. In addition, it has a positive and significant relationship between Hybrid lectures and students' cognitive abilities. It can be concluded that the more students' perceptions of hybrid lectures increase, the more students' cognitive abilities in learning innovation courses will increase.